'Hooray! Hooray! The End of the World has been Postponed!' Politics of Peace in the Adventures of Tintin?. (1st September 2013) - Rösch, Felix
<x xml:space="preserve">Abstract</x> Tintin is a cultural icon whose popularity has led to critical assessments accusing the comic of perpetuating orientalist and racist images. This article presents a different reading of Tintin by asking a more fundamental question: what understanding of the political is manifested in Tintin's Adventures? I argue that Tintin creates a political sphere that fosters an image of peace which does not eradicate conflicts, but facilitates them. Bildung, spatio‐temporal conditionality of knowledge, spheres of elasticity, and power ensure that they do not turn into violence. All these are characteristics of the comic and create a powerful visualisation of the human condition of politics.